Prevalence, Incidence, and Associated Factors of Possible Sarcopenia in Community-Dwelling Chinese Older Adults: A Population-Based Longitudinal Study - Chen, Zi; Ho, Mandy; Chau, Pui Hing (Frontiers in Medicine, 2022)
Purpose: The aim of this study was to assess the prevalence, incidence, and associated factors of possible sarcopenia in a nationwide representative sample of community-dwelling older Chinese population. Methods: This study used the data of participants aged 60 years and over from China Health and Retirement Longitudinal Study (CHARLS). Data on participants from three waves (2011-2015) of CHARLS were extracted. Possible sarcopenia was defined as low muscle strength or low physical performance, based on the AWGS 2019 consensus. We first described baseline prevalence and 4-year incidence of possible sarcopenia. Then multiple logistic regression and multivariable parametric proportional hazard model with Weibull distribution were used to examine the association of risk factors with baseline prevalence and 4-year incidence of possible sarcopenia respectively. Results: The prevalence of possible sarcopenia was 46.0%. The 4-year incidence of possible sarcopenia was 11.9 per 100 person-years. Multivariable analysis revealed that advanced age and depressive symptoms were associated with increased prevalence of possible sarcopenia, while receiving education and moderate or high physical activity (PA) were associated with lower risk of possible sarcopenia prevalence. For incidence, only advanced age was associated with increased risk of possible sarcopenia incidence. Conclusions: Our study revealed the substantial burden of possible sarcopenia and related risk factors in community-dwelling settings in China. It highlighted the importance of early detection and intervention in this subclinical group for prevention of sarcopenia.